Effective Leadership Styles In Elementary Educational Institutions In Indonesia - Zulfakar (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
This study aims to analyze the effectiveness of various principal leadership styles in improving the quality of primary education in Indonesia, with a specific focus on the context of primary education institutions on Lombok Island, West Nusa Tenggara. Using a descriptive qualitative approach with in-depth interviews, participant observation, and documentation studies, the study was conducted from March to May 2025. The findings indicate that a transformational leadership style has a significant influence on increasing teacher motivation and a collaborative learning culture in schools. Instructional leadership styles have also been shown to strengthen the principal's role in academic supervision and curriculum management. Meanwhile, a participatory style creates a democratic environment and increases teacher participation in decision-making. The situational style is considered effective in addressing various managerial conditions and challenges based on the contextual needs of each school. These findings emphasize the importance of flexibility and adaptive leadership combinations to create high-quality, inclusive, and sustainable learning environments. This research provides practical contributions to the professional development of principals and education policymakers at the regional and national levels.